The American LGBTQ Rights Movement An Introduction - Morgan, Kyle; Rodriguez, Meg (Open textbook library., 2020)
The American LGBTQ Rights Movement: An Introduction is a peer-reviewed chronological survey of the LGBTQ fight for equal rights from the turn of the 20th century to the early 21st century. Illustrated with historical photographs, the book beautifully reveals the heroic people and key events that shaped the American LGBTQ rights movement. The book includes personal narratives to capture the lived experience from each era, as well as details of essential organizations, texts, and court cases that defined LGBTQ activism and advocacy.